Quality Development Model of Management Islamic Religious Higher Education of Nahdltul Ulama - Subandi Subandi (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2020)
Quality management was a systemic mechanism in ensuring the sustainability of University. This lack of quality Islamic Religious Higher Education / Perguruan Tinggi Keagamaan Islam (PTKI) including Islamic Religious Higher Education NU / Perguruan Tinggi Keagamaan Islam Nahdlatul Ulama (PTKI NU) resulted less productive and competitive. The aim of this research was to describe the implementation of the development of high-quality management education in the Islamic Religious Higher Education of Nahdlatul Ulama or Perguruan Tinggi Keagamaan Islam Nahdlatul Ulama (PTKI NU). The method was qualitative based on multisitus through inductive analysis. The result showed that in planning of quality management education which was done by three PTKI NU was systemic and structured, where each University was oriented to improve the quality academic, with varying strategies through a needs analysis process. Next, the implementation of quality management aspects of higher education of three PTKI NU varied and has the same quality management aspects, namely carry out the procedure, preparation of human resources through training, financial support, and focus on in integration of two areas of quality : quality of students and Tri Darma Peguruan Tinggi. Furthermore, the evaluation aspects of quality management implemented mechanisms of self-evaluation, internal academic quality audit. Keywords: Quality Education Management, Quality Development Model Education Management